Pengaruh Bauran Pemasaran Terhadap Minat Beli Pada Counter Hamdalah Pulsa Tronik Di Tenggarong - Lestari, Puput Tri; Bahransyah, Bahransyah; Akbar, Ali (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract :Counter Hamdalah is one of the businesses engaged in Serving Pulsa tronik, friction pulse, data packet card, charging and electricity bills and taps online. Serving wholesale purchases of pulse agents, wholesale purchases of online bill payment agents, wholesale purchases of telephone cards and data packets (both in the city and out of town) are located at Jl. Lake aji, RT.23 No.23 Kelurahan. Malay, Tenggarong Sub-district established since 2010 by the owner Mr. Maidi. The purpose to be achieved in this study is to Know, What Price, Product, Promotion And Location has a significant influence on consumer buying interest In Counter Hamdalah Pulsa Tronik In Tenggarong and to Know, Of the four variables, which is the most dominant influence interest buy consumer On Counter Hamdalah Pulsa Tronik In Tenggarong From the results of the research hypothesis proposed by the researcher sebelunya is, Suspected variable Suspected factor price, product, promotion and location influence simultaneously to behavior intention (intention to buy) consumer at Counter Hamdalah Pulsa Tronik in Tenggarong. accepted and proven to be true. From the results of partial correlation test above shows the value of the variable of the most influential price where the t test research has been t arithmetic for the price variable followed by promotion variable, product, location, so that the sense variable is the most dominant variable influencing consumer buying intention. From the description, it can be concluded that the second hypothesis in this study "Suspected factor" price "has a dominant influence on behavior intention (intention to buy) consumers on Counter Hamdalah Pulsa Tronik in Tenggarong accepted and proven true.Keywords: Price, Product, Promotion, Location, Behaviour Interest.